Gender and Hand Dominance as Predictors of Forearm Disuse Osteoporosis in Patients with Traumatic Upper Extremity Injury - İlhan Karacan and Şafak Sahir Karamehmetoğlu and Mustafa Akif Sarıyıldız and Aynur Özen (Archives of Rheumatology, 2010)
Objective: Immobilization of an injured extremity leads to a rapid loss of bone. It is somewhat unclear why one traumatic insult should give rise to bone loss in one patient, while the identical insult in another patient does not. The aim of this study was to investigate whether there were other risk factors for disuse osteoporosis, in addition to immobilization. Materials and Methods: Ninety patients who had suffered a mechanical traumatic injury isolated to their upper extremity were included in this study. Effects of age, gender, types of injury, affected extremity (dominant or non-dominant), immobilization period, and remobilization period on the distal radius bone mineral density (BMD) of the injured side were investigated. BMD was measured using dual energy X-ray absorptiometry. Results: A low BMD (LBMD) was found in 31.1% of patients. The mean age was not significantly different between the normal BMD and LBMD groups. The female/male ratio was significantly higher in the LBMD group. The affected extremity was on the non-dominant side in 29.0% of the normal BMD group and in 53.5% of the LBMD group (p=0.045). The mean immobilization period was significantly higher in the LBMD group. There were no significant differences in the remobilization period between the LBMD and normal group. It was found that LBMD was only associated with female gender, non-dominant side injury and the immobilization period. Conclusion: Considering that non-dominant side injury, female gender and length of the immobilization may be important for development of disuse osteoporosis, we conclude that the prevention measures should be focused mainly on patients with these risk factors in order to reduce the risk of disuse osteoporosis. (Turk J Rheumatol 2010; 25: 137-40)